Answer: didn't know
Step-by-step explanation:
Came for points
Answer: 6 inches.
Step-by-step explanation:
Answer:
uh what is this address for or am i not supposed to be in this
Step-by-step explanation:
sorry if im getting in your buisness
An expression for the total cost of the daycare for Lucy's dog this week is T = 3F + 2H and the total cost is equal to $114.
<h3>How to write an expression for the total cost?</h3>
In this exercise, you're required to write an expression for the total cost of the daycare for Lucy's dog this week. Thus, we would assign a variable to the cost for full-day and half-day day care as follows:
- Let the cost for full-day be F.
- Let the cost for half-day be H.
Thus, the total cost of the daycare is given by:
T = 3F + 2H
Evaluating the expression, we have:
T = 3(28) + 2(15)
T = 84 + 30
T = $114.
Read more on expressions here: brainly.com/question/12189823
#SPJ1
Answer:
see below
Step-by-step explanation:
(ab)^n=a^n * b^n
We need to show that it is true for n=1
assuming that it is true for n = k;
(ab)^n=a^n * b^n
( ab) ^1 = a^1 * b^1
ab = a * b
ab = ab
Then we need to show that it is true for n = ( k+1)
or (ab)^(k+1)=a^( k+1) * b^( k+1)
Starting with
(ab)^k=a^k * b^k given
Multiply each side by ab
ab * (ab)^k= ab *a^k * b^k
( ab) ^ ( k+1) = a^ ( k+1) b^ (k+1)
Therefore, the rule is true for every natural number n